(untitled) (Economics and region, 2024)
This academic article delves into the critical theme of importance of the financial provision to stimulate economic growth in Ukraine. In an era of globalization and intense competition, an efficient financial system is paramount for sustainable national development. The study focuses on the experiences of three countries - Germany, Japan, and Korea - which, after enduring wartime conflicts, achieved significant economic progress. Analyzing these examples provides insights into financial strategies and tools that could be adapted in Ukraine to accelerate economic growth. The significance of this research lies in its ability to offer concrete recommendations for improving Ukraine’s financial provisioning and economic policies based on proven international practices. By studying the experiences of developed nations that transformed their post-war challenges into growth opportunities, Ukraine can discover keys to its own economic revival and sustainable development. Given Ukraine’s current challenges, especially in the wake of the 2022 Russian full scale military invasion, finding effective financial mechanisms for both internal and external economic growth is highly relevant. Thus, the article aims to identify and analyze successful financial provisioning strategies in Germany, Japan, and Korea, to determine their potential adaptation and application in the Ukrainian context. This approach enriches the theoretical foundation in this field and proposes practical directions for improving the country’s economic situation. The findings highlight the importance of effective financial systems, industrialization, modernization, government-private sector collaboration, and integration with international financial systems as pivotal for successful recovery. Ukraine has a unique opportunity to leverage these strategies to enhance its economy, lay robust foundations for future development, and integrate into the global economic system. These insights and recommendations, drawn from international post-war and economic crisis recovery experiences, are critical for Ukraine’s journey toward recovery and sustainable economic growth.